Developing an "experience framework" for an evidence-based information literacy educational intervention. Issue 2 (14th March 2016) - Forster, Marc
Abstract : Purpose: – The purpose of this paper is to describe how an "experience framework" for an evidence-based information literacy educational intervention can be formulated. Design/methodology/approach: – The experience framework is developed by applying the qualitative methodology phenomenography to the analysis of the variation in the experience of a phenomenon by a target group, making specific use of one of its data analysis methods, that pioneered by Gerlese Akerlind. A phenomenographic study's descriptions of the limited but related experiences of the phenomenon, and the detail of context and complexity in experience achieved through the Akerlind data analysis technique, are essential to a framework's structure and educationally valuable richness of detail. Findings: – The "experience framework", an example of which is set out in this paper, is formed from a detailed range of contexts, forms and levels of complexity of experience of a phenomenon, such as information literacy, in a group or profession. Groupings of aspects of that experience are used to formulate, through the application of variation theory, an education theory developed from previous phenomenographic research, learning contexts and aims which can form the focus of educational activities. Originality/value: – The framework can be used to form the basis of an evidence-based educational intervention to enrich the experience of any concept within LIS that Information professionals work to develop in their users.